Xenisme, emprunt et alternance codique comme moyens de l’expression culturelle dans le discours religieux de Tariq Ramadan - Sabrina Merzouk (Multilinguales)
Studies about language borrowing and code switching phenomenon are among the essentials in linguistics. These are used in a significant number of fields, but these phenomenon intrest us much more in their correclation with religious domain. In fact their usage in Tarik Ramadhan discourse is seen as essential since it permits the explanation and understanding of the religious discourse and address in a variéty of languages for communities that to not master Arabic. Langage borrowing and code switching help build a bridge between Arabic, Islam and French. These ways are considered necessary strategies that permit the popularization of the religious text and its understanding by other language interlocutors.